The last libertines - Craveri, Benedetta 1942- (New York Review Books, 2020)
"The Last Libertines, as Benedetta Craveri writes in her preface to the book, "tells the story of a group of young aristocrats living in the last days of the French monarchy, when it was still possible for the members of the elite to reconcile a way of life based on status and privilege with a belief, born of the Enlightenment, in the necessity for social transformation and the new ideals of justice, tolerance, and civility." Here we meet seven emblematic characters, whom Craveri has singled out not only for the "novelistic quality of their lives and loves" but also, perhaps above all, for the fully conscious way in which they confronted the crisis of the ancien régime while looking ahead to a new world being born. Displaying the aristocratic virtues of "pride, courage, fashionable elegance, culture, spiritedness, and conviviality," the duc de Lauzun, the comte de Segur, the vicomte de Segur, the duc de Brissac, the comte de Narbonnes, the comte de Vaudreuil, and the chevalier de Boufflers were not only masters of the art of seduction but true sons of the Enlightenment, all ambitious to play their part in bringing around the great changes that were in the air. When the French Revolution came, however, they were condemned to poverty, exile, and in some cases execution. Telling the parallel lives of these seven dazzling but little-remembered historical figures, Craveri brings to light a vanished civilization and dramatizes a time of turmoil that may be said to anticipate our own"--
Keywords: Geschichte 1789; Adel; Französische Revolution; Ancien régime; Frankreich; Nobility / France / Biography; France / History / Louis XVI, 1774-1793 / Biography; France / History / Louis XV, 1715-1774 / Biography; Nobility; France; 1715-1793; Biographies; History; Biografie